MUCOADHESIVE DELIVERY SYSTEMS USING CARRAGEENAN AND EUDRAGIT RLPO - Gloria RUÍZ (Universidad de Antioquia, 2009)
The objective of this research is a bioadhesive two layers controlled release tablets. The drug release and the physical properties of tablet formulations using two polymers (Carrageenan 934 and Eudragit RL PO) at three levels and at a combination of different ratios of the two polymers were evaluated. Formulation containing 40% total polymer level and a ratio of 1 Carrageenan to 1 Eudragit RLPO was the best formulationa. This formulation was tested in different dissolution medium and at different rotational speed. The drug release was 96.3% in phosphate buffer pH 7.4; 59.1% in 0.1 N HCl and 46.4% in distilled water. This study demonstrates the significance of the combination of two polymers for obtaining controlled release bioadhesive matrix and enhancing the characteristic of each polymer.